Tuberculosis Preventive Treatment (TPT) in India: A Qualitative Review - Jay Patel; Abhishek Sen; Sandeep Rai; Harsh Shah; Nisarg Desai (Preventive Medicine: Research & Reviews)
This review examines TB preventive treatment (TPT) implementation in India, highlighting barriers and potential solutions to improve outcomes under the National Tuberculosis Elimination Programme. Qualitative insights from beneficiaries, healthcare workers and policymakers reveal barriers and facilitators in TPT implementation. Key findings include requirements for strong policy commitment and customised interventions to address system-level barriers such as limited human resources, inadequate infrastructure, treatment adherence issues and community engagement barriers. The findings also revealed to create a responsive system that addresses the specific supportive system to ensure treatment adherence and successful outcomes. The integration of TB infection algorithm in existing TB diagnostic and treatment algorithms and comprehensive active case findings could result in positive outcome in reduction of TB, advancing India’s goal of TB elimination.